Diagnostic pathology of early systemic cancer: ERBB2 gene amplification in single disseminated cancer cells determines patient survival in operable esophageal cancer. Issue 4 (30th November 2017) - Hoffmann, Martin; Pasch, Sophie; Schamberger, Thomas; Maneck, Matthias; Möhlendick, Birte; Schumacher, Sarah; Brockhoff, Gero; Knoefel, Wolfram Trudo; Izbicki, Jakob; Polzer, Bernhard; Stoecklein, Nikolas H.; Klein, Christoph A.
Abstract : Early metastatic dissemination and evolution of disseminated cancer cells (DCCs) outside the primary tumor is one reason for the failure of adjuvant therapies because it generates molecular genotypes and phenotypes different from primary tumors, which still underlie therapy decisions. Since ERBB2 amplification in esophageal DCCs but not in primary tumor cells predict outcome, we aimed to establish an assay with diagnostic reliability for single DCCs or circulating tumor cells. For this, we evaluated copy number alterations of more than 600 single DCCs from multiple cancer types to define reference regions suitable for quantification of target regions, such as ERBB2 . We then compared ERBB2 quantitative PCR (qPCR) measurements with fluorescent in situ hybridization (FISH) data of various breast cancer cell lines and identified the aberration‐calling threshold. The method was applied to two independent cohorts of esophageal cancer patients from Hamburg ( n = 59) and Düsseldorf ( n = 53). We found a high correlation between the single cell qPCR assay and the standard FISH assay ( R = 0.98) and significant associations between amplification and survival for both patient cohorts (Hamburg (HH), p = 0.033; Düsseldorf (D), p = 0.052; pooled HH + D, p = 0.002) when applied to DCCs of esophageal cancer patients. Detection of a single ERBB2 ‐amplified DCC was the most important risk factor for death from esophageal cancer (relative risk = 4.22; 95% CI = 1.91–9.32; p < 0.001). In our study, we detected ERBB2 ‐amplified cells in 7% of patients. These patients could benefit from anti‐ERBB2 targeting therapies. Abstract : What's new? About half of esophageal cancer patients are diagnosed with early disease and are eligible for surgical resection, increasing their chances of survival. To better predict prognosis in these patients, markers strongly indicative of early systemic cancer are needed. This report describes an assay for quantifying gene amplification of the tyrosine kinase ERBB2 in single disseminated cancer cells (DCCs), which are targets of adjuvant therapies. In DCCs of esophageal cancer patients in two separate cohorts, ERBB2 amplification was associated with survival. Moreover, ERBB2 gene amplification in DCCs was the most important factor for predicting death in uni‐ and multivariable analysis, suggesting that it is prognostically relevant in esophageal cancer and that targeting of ERBB2 in such high‐risk patients could improve their outcome.